Space-resolved in-plane moduli of graphene oxide and chemically derived graphene applying a simple wrinkling procedure - Kunz, Daniel A.; Feicht, Patrick; Goedrich, Sebastian; Thurn, Herbert; Papastavrou, Georg; Fery, Andreas; Breu, Josef (Advanced Materials, 2013)
Mapping the in-plane moduli: A simple wrinkling process on a deformable substrate requiring only readily available topographical atomic force microscopy (AFM) imaging allows space-resolved determination of the mechanical properties of single graphene oxide and chemically derived graphene sheets. The lateral resolution in the sub-micrometer range delivers unique insights into the defect distribution within the nanoplatelets. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: atomic force microscopy; graphene; mechanical properties; nanoplatelets; wrinkling